A Living Heritage Approach Toward Sustainability of Islamic City in The Northern Coastal of Java, Indonesia - Atik Suprapti (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2021)
Cultural diversity is one of the global issue underlined by UN. Indonesia known as a very rich country has more than 300 ethnic cultures. One of them is Islamic architecture and cities that spread in the North Coast of Java. In the span of 6 centuries, we can still witness the existence of these works as living heritage that saves tangible and intangible culture. The role of the community is very significant which are take care, plan and develop for the next generation. However, the changes that have occurred are caused by urbanization, and the shift in the political and economic map poses a threat to the sustainability of this legacy. The purpose of writing this article is to provide views on the importance of an approach to the process of preserving living cultural heritage by involving community participation in order to maintain the sustainability of cultural heritage. The locus in the North Coast of Java is based on the consideration that the cities in this region inherit the distinctive Islamic culture of the Coastal Java and its dynamics. The digital-legacy approach combines the use of information technology in this case is Web GIS for archiving artifact data. Meanwhile, the living heritage approach encourages community participation to play an active role with stakeholders on an ongoing basis in the preservation of artifacts. Kudus Kulon is an interesting and unique case with the Gusjigang community who have cared for Omah Joglo Pencu for almost three centuries. Architectural sustainability – Muslim cities include historical and cultural sustainability, function, and maintenance